GAMBARAN PENGETAHUAN MAHASISWA KEPERAWATAN TENTANG PENULARAN INFEKSI NOSOKOMIAL DI RUMAH SAKIT PTPN II BANGKATAN BINJAI TAHUN 2017 - Ilham Syahputra Siregar (Jurnal Riset Hesti Medan, 2017)
Nosocomial infection is an infection that appears as long as a person is hospitalized and begins to show a symptom as long as someone is being treated or after being treated and showing symptoms after 72 hours the patient is in the hospital. Infeki nosocomial is still the main cause of high morbidity and mortality in the world. This infection causes 1.4 million deaths every day around the world (WHO, 2015). In Indonesia the prevalence of nosocomial infections is quite high at 6% - 16% with an average of 9.8% of nosocomial infections that occur due to surgical wound infections (ILO). Based on the survey that the researchers did, the incidence of nosocomial infections showed a prevalence rate of around 1.5% of cases that occurred at PT Departure II Bangkat Binjai Hospital. The purpose of this study was to find out the description of Nursing Students 'knowledge about the transmission of nosocomial infections in PTPN II Hospital Binjai Departure in 2017. The specific objective of this study was to identify nursing students' knowledge about contacting nosocomial infections directly, through common vehicle, by air and inhalation, or through vectors at PTPN II Hospital Binjai Departure in 2017. The reason is the availability of samples expected by researchers and for time and cost efficiency. Based on the results of research conducted by the researcher, it can be seen that the description of the level of knowledge of nursing students about the transmission of nosocomial infections in PTPN II Bangkat Binjai hospital is mostly well-informed based on direct contact transmission of 15 people (75%), through common vehicles of 10 people ( 50%), airborne and inhalation transmission as many as 14 people (70%) and vector-borne transmission as many as 14 people (70%). Suggestions for hospitals and health workers should be able to improve the quality of health by making better health surveillance to reduce the number of nosocomial infections.Keywords: Knowledge Overview, Nosocomial Infection